Pengaruh Pengetahuan, Kompensasi dan Komitmen Organisasi terhadap Kinerja Anggota DPRD se-Provinsi Kepulauan Riau dengan Motivasi Kerja sebagai Variabel Intervening - Respationo, Soerya; Indrayani, Indrayani; Satriawan, Bambang (Universitas Batanghari Jambi, 2025)
This research aims to determine whether there is a direct influence of knowledge, compensation, organizational commitment and work motivation on performance and a direct influence of knowledge, compensation and organizational commitment on work motivation. As well as the indirect influence of knowledge, compensation, organizational commitment on performance through work motivation. The samples from this research were members of the Riau Islands Provincial Council. A total of 152 questionnaires were distributed and all were returned, using a probability sampling technique. The results of the research can be concluded that the variables, knowledge and organizational commitment have a significant positive direct effect on performance. Meanwhile, compensation and work motivation variables have a positive and insignificant direct effect on performance. The indirect effect of the knowledge variable, compensation on performance through work motivation has a significant positive effect and organizational commitment on performance through work motivation has an insignificant effect. The coefficient of determination R square adjusted for knowledge, compensation, organizational commitment and work motivation on performance is 0.200 and knowledge, compensation, organizational commitment and work motivation is 0.272